Shipboard ADCP and LADCP current data from Poseidon cruise POS516 (2017) - Maren Walter (PANGAEA, 2018)
This data collection contains current measurements with Lowered Acoustic Doppler Current Profiler (LADCP) on seven repeat stations along a tidal beam south of the Azores and upper ocean current data from shipboard Acoustic Doppler Current Profiler (ADCP) data, Poseidon cruise POS516.